Pertumbuhan Fragmen Karang Polyphyllian talpina dengan Metode Transplantasi Mini-floating Nursery di Perairan Teluk Awur Jepara - Lukytasari, Jenny; Wijayanti, Diah Permata; Munasik, Munasik (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Ornamental coral trade which is taken directly from nature is a source of revenue for the Indonesian economy, but on the other hand it is also a threat to coral reef conservation. Along with the increasing number of the ornamental coral exports it must be balanced with the conservation effort through coral transplantation. One of coral reef species that can regenerate and widely traded is Polyphillia talpina. Transplantation method used is the mini-floating nursery method, the coral transplantation method performed by a state hovering in the water column. This study aims was to determine the growth of solitary corals which were transplanted by mini-floating nursery method and to determine the process of regeneration that occurs with mini-floating nursery transplant method in Teluk Awur, Jepara. Growth of the highest coral transplant P. talpina seen in coral fragments with the size of 4 cm with a gain of 0,44 cm difference with regeneration process and the addition of the highest number of mouth was also to 70,12%. Statistical analysis showed there were no significant differences (p = 0,652) on growth and the initial size of the two fragments.